Beauty and the big business: A qualitative investigation of the development and implementation of the CVS Beauty Mark. (June 2022) - Danthinne, Elisa S.; Giorgianni, Francesca E.; Austin, S. Bryn; Rodgers, Rachel F.
Abstract: Detrimental effects of retouched media imagery on body image among women have led to calls to increase transparency regarding the use of digital modification. CVS Health, a large US-based beauty retailer, announced in 2018 its intention to implement across its beauty department imagery two labels: a "Beauty Mark " label to indicate a retouch-free image, and a second label disclosing digital modification. The aim of the present study was to explore the motivations, facilitators, and barriers to its implementation. In-depth individual interviews (n = 11) were conducted with professionals involved in the conceptualization, development, artistic vision, and implementation of the initiative. Thematic analysis revealed three themes: (1) CVS's perception that the campaign as a good fit; (2) the marketing of "empowerment" to generate profit as well as a desired outcome; and (3) desire to exemplify a value-driven company model and contribute sustainably to broader values such as diversity and body positivity. These findings may help to identify ways in which to create larger scale change within media imagery. Highlights: In 2018 CVS introduced the "Beauty Mark " label to indicate retouched-free images. Interviews were conducted with professionals involved in the initiative. Thematic analysis revealed three important themes related to the brand's mission as well as tensions around profit. Understanding the motivations for such initiatives may help to change media imagery.